EKSTRAKSI ASPAL ASBUTON UNTUK CAMPURAN BERASPAL PANAS - Furqon Affandi (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Asbuton is Indonesian natural resource with a large amount of deposit, but has not been effectively utilized. On the other hand Indonesia imports asphalt about 650,000 tonnes per annum. Technology improvement to produce Asbuton with can be effectively used both in mixture and in asphalt content is immediately required. This article describes the properties of Asbut on resulted from extraction technology with has little mineral content ( < 1% ) and also describes properties of bituminous mixtures using bitumen Asbuton and asphalt cement pen grade 60 by Marshall method. The stiffness modulus properties of bituminous mixtures, resistance against deformation or accumulative strain due to repeated loading were examined in various temperatures. The test results show that bitumen of Asbuton extraction and asphalt mixes using bitumen Asbuton, generally has good performance compared to conventional asphalt cement especially for tropical area such as Indonesia.